Ecological Risk Assessment of Metal Pollution along Greater Cairo Sector of the River Nile, Egypt, Using Nile Tilapia, Oreochromis niloticus, as Bioindicator - Wael A. Omar; Wafai Z. A. Mikhail; Hanaa M. Abdo; Tarek A. Abou El Defan; Mamdouh M. Poraas (Journal of Toxicology)
The present work aims to evaluate seasonal metal pollution along Greater Cairo sector of the River Nile, Egypt, using wild Nile tilapia, Oreochromis niloticus, as bioindicator and to conduct a risk assessment for human consumers. Greater Cairo is the largest populated area along the whole course of River Nile with a wide range of anthropogenic activities. Effects of metal pollution on fish body indices were studied using condition factor (CF) and scaled mass index (SMI). Metal pollution index (MPI) showed that the total metal load in fish organs followed the follwoing order: kidney > liver > gill > muscle which gives a better idea about the target organs for metal accumulation. Metal concentrations in fish muscle (edible tissue) showed the following arrangement: Fe > Zn > Cu > Mn > Pb > Cd. Metal’s bioaccumulation factor (BAF) in fish muscle showed the following arrangement: Zn > Cu > Fe > Mn > Cd and Pb. The hazard index (HI) as an indicator of human health risks associated with fish consumption showed that adverse health effects are not expected to occur in most cases. However, the metals’ cumulative risk effects gave an alarming sign specifically at high fish consumption rates.